SOSIALISASI DESA SADAR HUKUM DALAM MENINGKATKAN KESADARAN HUKUM MASYARAKAT DESA JAMBANAN KECAMATAN SIDOHARJO SRAGEN - Liana Endah Susanti; Dwi Edi Wibowo (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2023)
The Community Service Program partners with the people of Jambanan Village, Sidoharjo District, Sragen Regency. There needs to be effective and sustainable socialization of the Law Awareness Family (Kadarkum) to overcome the lack of understanding of the law so that people really understand the importance of law. The activity method begins with the preparation stage, then the implementation stage and finally the reporting stage which is planned to be completed within 3 months. The research results show. The results and outputs of the activities after the implementation of the program have been achieved, that is, after the socialization was carried out, the community experienced an increase in knowledge and understanding of the importance of legal awareness in social life, therefore there is a need for synergy between related Ministries or Institutions in formulating programs that are sustainable and evaluated annually, one of which is through integrated legal counseling so that the program is expected to be focused, not overlapping, right on target and effective in disseminating information in order to increase legal awareness of the people of Jambanan Village, Sidoharjo District.Keywords: Village/Kelurahan Formation, Legal Awareness.Â